A nurse-led randomised controlled trial of a structured educational programme for patients starting warfarin therapy. (August 2014) - Moss, RC; Lowe, GC; Frampton, CA; Revell, P
Aim: To investigate the effect of a randomised controlled trial of a nurse-led structured educational programme compared to standard care on patient knowledge when starting anticoagulant therapy with warfarin. Methods: 45 patients commencing warfarin during an inpatient admission were randomised into either a control group receiving 'usual' care, or an experimental group with structured counselling and provision of an educational video. Identical questionnaires assessing knowledge of anticoagulation therapy were applied at discharge and again 3 months later. Results: Patients receiving a structured educational approach had significantly better knowledge about their therapy both at hospital discharge and at 3 months post discharge ( p  = <0.001 and p  = 0.038 respectively). Secondary outcomes measured also showed a higher level of patient satisfaction ( p  = 0.017) and time in target INR range (56.7% versus 48.1%) in the educational arm. Conclusions: A formal and structured nurse-led educational package at the initiation of anticoagulant treatment with warfarin treatment improves patient knowledge.